If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(w + -3) = 4(3 + -1w) Reorder the terms: 8(-3 + w) = 4(3 + -1w) (-3 * 8 + w * 8) = 4(3 + -1w) (-24 + 8w) = 4(3 + -1w) -24 + 8w = (3 * 4 + -1w * 4) -24 + 8w = (12 + -4w) Solving -24 + 8w = 12 + -4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '4w' to each side of the equation. -24 + 8w + 4w = 12 + -4w + 4w Combine like terms: 8w + 4w = 12w -24 + 12w = 12 + -4w + 4w Combine like terms: -4w + 4w = 0 -24 + 12w = 12 + 0 -24 + 12w = 12 Add '24' to each side of the equation. -24 + 24 + 12w = 12 + 24 Combine like terms: -24 + 24 = 0 0 + 12w = 12 + 24 12w = 12 + 24 Combine like terms: 12 + 24 = 36 12w = 36 Divide each side by '12'. w = 3 Simplifying w = 3
| X^3-24x=0 | | -2/3t+2-3/4t=-4 | | 2/5x=3/4 | | a^2+50=0 | | q+7-2(q-2)=3(2q+1)+5q | | 1/2x+5+1/3x-5 | | 2a-10=2 | | 13n=42-3 | | 7x+6=9x | | 3x/x-5-5/x-2 | | 13x+195=13(3x+15) | | 4/3z-7+2/3z=-1 | | 88-5x=2x+11 | | -6/x-5-8/x+7 | | 15X+3-7X+4-8X=0 | | 144x^3-258x^2+105x=0 | | pi=3.1416 | | 2x+6/4+5x-2/8 | | 1/2t=-13 | | 7(x-1)=2(2x+4) | | 4x+z=19 | | X+3.5=8.8 | | -x^2-6x+5y^2+10y=22 | | 7(x-5)+14=-7 | | 6x+3=8x-3x | | 12t^2+32t=12 | | 1/2y=1.5 | | 2n/5=30 | | 3z+5z-2=0 | | 261=195-u | | 3x^5-39x^3+108x=0 | | 4x-3/1-6x=x-7/x+9 |